Shopping while black: consumer racial profiling in America - Gabbidon, Shaun L. (Criminology and justice studies, 2020)
Shopping While Black An Introduction WithShaun L. Gabbidon, George E. Higgins -- Public Opinion on Consumer Racial Profiling WithShaun L. Gabbidon, George E. Higgins -- Racial Profiling Victimization WithShaun L. Gabbidon, George E. Higgins -- Consumer Racial Profiling Litigation State and Federal Case Studies WithShaun L. Gabbidon, George E. Higgins -- Conclusion WithShaun L. Gabbidon, George E. Higgins.